'Click' polymer of carbon nanotubes for superhydrophobic glass and leather. Issue 2 (30th May 2017) - Krishnamurthy, Munusamy; Murugan, Pachiyappan; Murali, Adhigan; Jaisankar, Sellamuthu Nagappan; Mandal, Asit Baran; Samanta, Debasis
Abstract : Copper (I)-catalyzed 1, 3-dipolar cycloaddition reaction of azide–alkyne is called a 'click' reaction. It is an adaptable tool for preparing multifunctional materials. In this paper, the authors report click polymerization of single-walled carbon nanotubes (SWCNTs) with thiophene/aryl compounds and their electronic/spectroscopic properties and applications. The various spectroscopic and microscopic studies (Fourier transform infrared (FT-IR), Raman, X-ray photoelectron spectroscopy (XPS), field emission scanning electron microscopy, nuclear magnetic resonance and ultraviolet–visible) confirmed the success of the polymerization. The superhydrophobicity of the materials was studied by contact angle measurement. The FT-IR studies indicated the disappearance of azide residues in the polymeric products, and the Raman studies exhibited a high degree of covalent functionalization of SWCNTs. The XPS data show the presence of polymeric elements in the click copolymer of SWCNTs. Dynamic light scattering studies confirmed the broad size distribution of the materials. Moreover, the thermogravimetric analysis revealed the high thermal stability of the polymer. Finally, wettability measurements of leather and glass surfaces after coating with the copolymer of SWCNTs show high water contact angles of 155 and 163°, respectively. The results were well reproduced, and these superhydrophobic characteristics indicate the material's efficiency for designing various superhydrophobic surfaces.